2018
DOI: 10.1074/mcp.ra118.000892
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acetylation and Phosphorylation on Subunit Interactions in Three Large Eukaryotic Complexes

Abstract: Protein post-translational modifications (PTMs) have an indispensable role in living cells as they expand chemical diversity of the proteome, providing a fine regulatory layer that can govern protein-protein interactions in changing environmental conditions. Here we investigated the effects of acetylation and phosphorylation on the stability of subunit interactions in purified complexes, namely exosome, RNA polymerase II and proteasome. We propose a computational framework that consists of conformational sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 75 publications
1
18
0
Order By: Relevance
“…Similarly to our previous results on a smaller dataset [24], the comparison of the binding energy decomposition between non-modified and modified complexes revealed that lysine acetylation more frequently contributes to binding in a locally stabilizing fashion, while the opposite is true for phosphorylations (Figs 2 and S4). These effects might be the consequence of the local changes introduced by the respective modifications: while phosphorylation brings about a negative charge that must be compensated by neighboring positively charged residues, PLOS COMPUTATIONAL BIOLOGY acetylation diminishes the charge from the lysine side chain.…”
Section: Acetylation and Phosphorylation Have Different Local Contributions To Bindingsupporting
confidence: 82%
“…Similarly to our previous results on a smaller dataset [24], the comparison of the binding energy decomposition between non-modified and modified complexes revealed that lysine acetylation more frequently contributes to binding in a locally stabilizing fashion, while the opposite is true for phosphorylations (Figs 2 and S4). These effects might be the consequence of the local changes introduced by the respective modifications: while phosphorylation brings about a negative charge that must be compensated by neighboring positively charged residues, PLOS COMPUTATIONAL BIOLOGY acetylation diminishes the charge from the lysine side chain.…”
Section: Acetylation and Phosphorylation Have Different Local Contributions To Bindingsupporting
confidence: 82%
“…It was notably shown to decorate three-quarters of the detected proteins in human cells to various degrees [73]. A major role played by phosphorylation is intervening in the stabilization or destabilization of protein-protein interactions [74][75][76][77][78][79]. Therefore, the knowledge on the phosphorylation status of HCMV virion proteins may help in understanding how this particular PTM influences the assembly and stability of this multiprotein system.…”
Section: Ms-based Characterization Of the Hcmv Virion Phosphoproteomementioning
confidence: 99%
“…Therefore, prioritization strategies are crucial to facilitate the discovery of highly relevant phosphosites 10 . Different methodologies have been proposed, including identifying phosphosites that are highly conserved 11,12 , located at interface positions [13][14][15] , showing strong regulation, or combinations of such features 10,16 . Mutational studies have also been used to characterize relevant phosphorylations 17 , but cannot yet be applied to human phosphorylation at scale.…”
mentioning
confidence: 99%